Object-Oriented Application Development Using Microsoft Visual Basic .NET - E. Reed Doke
Take the object-oriented approach! Utilize Microsoft's powerful new development language, Visual Basic .NET, to explore object-oriented programming with object-oriented system development. Perfect for the CIS/MIS student